2022
DOI: 10.3390/molecules27020344
|View full text |Cite
|
Sign up to set email alerts
|

Solid Lipid Nanoparticles Administering Antioxidant Grape Seed-Derived Polyphenol Compounds: A Potential Application in Aquaculture

Abstract: The supply of nutrients, such as antioxidant agents, to fish cells still represents a challenge in aquaculture. In this context, we investigated solid lipid nanoparticles (SLN) composed of a combination of Gelucire® 50/13 and Precirol® ATO5 to administer a grape seed extract (GSE) mixture containing several antioxidant compounds. The combination of the two lipids for the SLN formation resulted in colloids exhibiting mean particle sizes in the range 139–283 nm and zeta potential values in the range +25.6–43.4 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…The bands at 1128 and 1062 cm −1 can be attributed, respectively, to the C-C symmetric and antisymmetric stretching vibrations, and it allowed for the calculation of the I 1115 /I 1050 cm −1 ratio referring to the fluidity within the hydrocarbon chains (Table 2). In the Raman spectra of the SLNs, bands in the region between 800 and 850 cm −1 were found and ascribed to twisting and rocking vibrations [21,23]. In the lyophilized plain SLNs, DA-co-GSE-SLNs-sucrose and GSE-ads-DA-SLNs, the same Raman pattern of the lipid Gelucire was detected, and interestingly, no band intensity change was noticed.…”
Section: Raman Spectroscopymentioning
confidence: 81%
See 3 more Smart Citations
“…The bands at 1128 and 1062 cm −1 can be attributed, respectively, to the C-C symmetric and antisymmetric stretching vibrations, and it allowed for the calculation of the I 1115 /I 1050 cm −1 ratio referring to the fluidity within the hydrocarbon chains (Table 2). In the Raman spectra of the SLNs, bands in the region between 800 and 850 cm −1 were found and ascribed to twisting and rocking vibrations [21,23]. In the lyophilized plain SLNs, DA-co-GSE-SLNs-sucrose and GSE-ads-DA-SLNs, the same Raman pattern of the lipid Gelucire was detected, and interestingly, no band intensity change was noticed.…”
Section: Raman Spectroscopymentioning
confidence: 81%
“…As for the investigation aimed to evidence possible interactions with nasal fluids of cryoprotected SLNs, we have recently reported that a useful approach is based on the use of Raman spectroscopy [21], herein applied on the freeze-dried SLNs as such and after incubation in the SNF medium. In particular, as mentioned above, it has been shown that the I 2890 /I 2850 ratio is an indication of chain packing and conformational disorder, while the I 1115 /I 1050 cm −1 ratio refers to the fluidity within the hydrocarbon chains [21]. In the case herein examined, interaction with SNF is based on band deformation observed in the ranges 800-940 cm −1 , 1000-1200 cm −1 , 1230-1350 cm− 1 and 2800-3000 cm −1 , leading to a flattened shape, probably due to the presence of the SNF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Precirol s ATO 5 (Precirol), a glyceryl distearate with a moderate melting point (50-60 1C), is commonly used as the core of the matrix in various lipidic formulations and has shown the ability to control the drug release from the delivery systems. [37][38][39] Therefore, we sought to develop a nanoparticulate formulation comprising of Eudragit RL100 s , Precirol s ATO5 and mPEG-PLA.…”
Section: Resultsmentioning
confidence: 99%